Pengaruh Jenis Pupuk Organik terhadap Pertumbuhan dan Hasil Beberapa Kultivar Ubi Jalar (Ipomoea batatas L.) di Lahan Kering - Syprianus Ceunfin; Maria goreti Bere (Fakultas Pertanian, Universitas Timor, 2022)
This research is to find out Effects Species Organic Fertilizers for growth and yield of few cultivar sweet potato (Ipomoea batatas, L.) on the arid land. The research was conducted in September 2020-December 2020 in the Faculty of Agriculture experimental garden, University of Timor, at Sasi Village, Kefamenanu, Timor Tengah Utara (TTU), using 2 factorial Stripe Plot Design (RPD). The first factor is the type of species organic fertilizers be composed of three stage namely: Control= without organic fertilizers, cow manure, goat manure. The second factor is cultivar sweet potato be composed of two level namely: red color sweet potato and purple color sweet potato. Comprise six combination treatment, was repeated 3 times so there are 18 units of research.The results research showed that there was interaction between the tipes of fertilizers treatment and sweet potato cultivar on the observed parameters of soil moisture content 80 HST, soil volume weight 40 HST, net assimilation rate, plant growth rate and harvest index.The application of types of fertilizer and cultivar of sweet potato, tipe of organic fertilizer of goat manure 64 g or equal with 10 t/ha produced the heaviest sweet potato tubers is 4,84 t/ha and cultivar sweet potato red color produced sweet potato tubers heaviest 3,49 t/ha.